Let \( \mathbf{u}=\langle 0,-3,0\rangle \) and \( \mathbf{v}=\langle 0,3,0\rangle \). Compute \( |\mathbf{u} \times \mathbf{v}| \). Then sketch \( \mathbf{u}, \mathbf{v} \), and \( \mathbf{u} \times \mathbf{v} \). \( |\mathbf{u} \times \mathbf{v}|=\square \) (Simplify your answer, including any radicals. Use integers or fractions for any numbers in the expression.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To compute \( |\mathbf{u} \times \mathbf{v}| \), let's first find the cross product \( \mathbf{u} \times \mathbf{v} \). Given: \[ \mathbf{u} = \langle 0, -3, 0 \rangle, \quad \mathbf{v} = \langle 0, 3, 0 \rangle, \] the formula for the cross product \( \mathbf{a} \times \mathbf{b} \) in three dimensions is given by the determinant of the following matrix: \[ \mathbf{a} \times \mathbf{b} = \begin{vmatrix} \mathbf{i} & \mathbf{j} & \mathbf{k} \\ 0 & -3 & 0 \\ 0 & 3 & 0 \end{vmatrix} \] Calculating this determinant: \[ \mathbf{u} \times \mathbf{v} = \mathbf{i}(0 \cdot 0 - 0 \cdot 3) - \mathbf{j}(0 \cdot 0 - 0 \cdot 0) + \mathbf{k}(0 \cdot 3 - (-3) \cdot 0) = \mathbf{0} - \mathbf{0} + \mathbf{k}(0) = \langle 0, 0, 0 \rangle \] So, \( \mathbf{u} \times \mathbf{v} = \langle 0, 0, 0 \rangle \). Now, to find the magnitude \( |\mathbf{u} \times \mathbf{v}| \): \[ |\mathbf{u} \times \mathbf{v}| = \sqrt{0^2 + 0^2 + 0^2} = 0. \] Thus, \( |\mathbf{u} \times \mathbf{v}| = 0 \). Now, as for the sketch: You can visualize \( \mathbf{u} \) pointing straight down on the negative y-axis while \( \mathbf{v} \) points straight up on the positive y-axis. They are collinear (lying along the same line) and thus do not create a plane with a non-zero area—hence the cross product being the zero vector. The sketch would show both vectors aligned along the y-axis, with the origin in the middle, but no vector emerging from their cross product since it is the zero vector. Final answer: \[ |\mathbf{u} \times \mathbf{v}| = 0. \]